2013
DOI: 10.1155/2013/597034
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions across the GNB3C825TPolymorphism in an Elderly Italian Population

Abstract: To verify whether the C825T polymorphism of the GNB3 influences the response to neuropsychological tests, mini-mental state examination, digit span (DS), immediate and delayed prose memory, memory with interference at 10 and 30 seconds (MI 10 and 30), trail making tests (TMTs) A and B, abstraction task, verbal fluency (VF) test, figure drawing and copying, overlapping figures test and clock test were performed in 220 elderly men and women free from clinical dementia and from neurological and psychiatric diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Participants were seen by a neuropsychologist at an ad hoc hospital unit. Cognitive assessment was performed by mini‐mental state examination (MMSE) and a comprehensive neuropsychological battery of eight validated paper and pencil tests (Figure ) administered in a single session of approximately 2 h .…”
Section: Methodsmentioning
confidence: 99%
“…Participants were seen by a neuropsychologist at an ad hoc hospital unit. Cognitive assessment was performed by mini‐mental state examination (MMSE) and a comprehensive neuropsychological battery of eight validated paper and pencil tests (Figure ) administered in a single session of approximately 2 h .…”
Section: Methodsmentioning
confidence: 99%
“…At the initial visit, cognitive assessment was performed by a MiniMental State Examination 32 and by a comprehensive neuropsychological battery of validated paper-and-pencil tests standardized for Italian people 33 administered in a single session lasting ≈2 hours. Details are described Cognitive Pattern Assessment section of onlineonly Data Supplement and in Table S1 in the online-only Data Supplement.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…Studies have also reported that CHRFAM7A [58], ACHE (acetylcholinesterase (Cartwright blood group) [305], HP (haptoglobin) [306], SELENBP1 [63], BASP1 [72], CHRNA1 [307], RPTN (repetin) [76], IL33 [308], TACR1[309], SHANK3 [310], ALOX12B [311], HPN (hepsin) [312], GFAP (glial fibrillary acidic protein) [84], CACNB2 [313], MYT1 [314], NOTCH3 [315], TERT (telomerase reverse transcriptase) [316], GNB3 [317], EGR3 [318], BSN (bassoon presynaptic cytomatrix protein) [319], CUX2 [320], GDF15 [321], CXCL8 [322], MAGI1 [95] and PAH (phenylalanine hydroxylase) [323] are necessary for BD development. S100A12 [324], CDH1 [325], S100A9 [326], ANK1 [327], KCNH2 [328], HP (haptoglobin) [329], FRMD4A [330], SNCA (synuclein alpha) [331], FBXO7 [332], PINK1 [333], B2M [334], KCNH3 [335], CA2 [336], FUZ (fuzzy planar cell polarity protein) [337], UBB (ubiquitin B) [338], C5AR1 [339], CBS (cystathionine beta-synthase) [340], F12 [341], TSPAN5 [342], NQO2 [343], NDUFA1 [344], SRXN1 [345], BASP1 [346], GPX1 [347], OLIG2 [348], EFHC2 [349], FOXA1 [350], PAX4 [351], BGN (biglycan) [352], IL33 [353], LRIG3 [354], GJA1 [355], SHANK3 [356], ARC (activity regulated cytoskeleton associated protein) [357], GFAP (glial fibrillary acidic protein) [358], UNC13A [359], MSTN (myostatin) [360], HSPG2 [361], TERT (telomerase reverse transcriptase) [362], GNB3 [363], L1CAM [364], CALB1 [365], RYR2 [366], MYO15A [367], MYH11 [368], GDF15 […”
Section: Discussionmentioning
confidence: 99%